Gene–environment correlation in the development of adolescent substance abuse: Selection effects of child personality and mediation via contextual risk factors. (11th February 2013) - Hicks, Brian M.; Johnson, Wendy; Durbin, C. Emily; Blonigen, Daniel M.; Iacono, William G.; McGue, Matt
Abstract: We used a longitudinal twin design to examine selection effects of personality traits at age 11 on high-risk environmental contexts at age 14 and the extent to which these contexts mediated risk for substance abuse at age 17. Socialization at age 11 (willingness to follow rules and endorse conventional values) predicted exposure to contextual risk at age 14. Contextual risk partially mediated the effect of socialization on substance abuse, though socialization also had a direct effect. In contrast, boldness at age 11 (social engagement and assurance, thrill seeking, and stress resilience) also predicted substance abuse directly but was unrelated to contextual risk. There was substantial overlap in the genetic and shared environmental influences on socialization and contextual risk, and genetic risk in socialization contributed to substance abuse indirectly via increased exposure to contextual risk. This suggests that active gene–environment correlations related to individual differences in socialization contributed to an early, high-risk developmental trajectory for adolescent substance abuse. In contrast, boldness appeared to index an independent and direct genetic risk factor for adolescent substance abuse.